Response of sugarcane (Saccharum sp.) varieties to embryogenic callus induction and in vitro salt stress - GANDONOU, GBOSSÈGNON CHRISTOPHE BERNARD; ABRINI, Jamal; IDAOMAR, Mohamed; SKALI SENHAJI, Nadia (My University, 2005)
Response of three varieties of sugarcane (Saccharum sp.) to callus induction, embryogenic callus production and in vitro salt tolerance was studied. For callus induction and embryogenic callus production, leaf bases segments were subjected to in vitro culture on Murashige and Skoog (MS) medium supplemented with 3 mg l-1 2,4 Dichlorophenoxyacetic acid for 4 weeks. To evaluate salt tolerance of the varieties, growing calli were exposed after two subsequent subcultures (4 weeks each) to different concentrations of NaCl (0, 17, 34, 68 and 102 mM) added to the culture medium for 4 weeks. Comparision of genotypes was based on callus induction percentage, embryogenic callus production percentage and relative fresh weight growth (RFWG). For salt tolerance, necrosis percentage and relative fresh weight growth of callus were used. The three varieties responded well to callus induction with a percentage of induction about 82, 84 and 100% for CP70-321, NCo310 and CP65-357, respectively. The high percentages of embryogenic callus obtained for the three varieties indicated that these varieties have a high capacity for embryogenic callus production. Relative fresh weight growth of callus was about 1.076, 1.282 and 0.925 for CP70-321, NCo310 and CP65-357, respectively. NaCl effect resulted in calli necrosis and a reduction of their growth. However, growing calli derived from varieties CP70-321 and NCo310 showed less necrosis percentages and less relative fresh weight growth reduction under salt stress. They appeared to be more salt tolerant in vitro than CP65-357.
Keywords: Callus induction; embryogenic callus culture; in vitro salt tolerance; Saccharum sp.